Evolution of Trypanosoma cruzi: clarifying hybridisations, mitochondrial introgressions and phylogenetic relationships between major lineages - Tomasini, Nicolás (2015)
Different models of evolution of Trypanosoma cruzi have been proposed. These models suggest scarce events of genetic exchange in the evolutionary history of this parasite. In addition, the debate focused on the existence of one or two hybridization events during the evolution of T. cruzi lineages. Here we reviewed literature and analyzed available sequence data in order to clarify the phylogenetic relationships among lineages. We observed that TcI, TcIII and TcIV form a monophyletic group and consequently TcIII and TcIV are not, as previously suggested, TcI-TcII hybrids. Particularly, TcI and TcIII are sister groups that diverged around the same time that a widely distributed TcIV was splitted into two clades (TcIVS and TcIVN). In addition, we collected evidence that TcIII received the TcIVS kDNA by introgression at several opportunities. Different demographic hypotheses (surfing and asymmetrical introgression) may explain the origin and expansion of the TcIII group. Considering these hypotheses, genetic exchange should have been relatively frequent between TcIII and TcIVS in the geographic area in which their distributions were superimposed. In addition, our results support the hypothesis that two independent hybridization events gave origin to TcV and TcVI. Consequently, TcIVS kDNA was first transferred to TcIII and later to TcV and TcVI in TcII/TcIII hybridization events.